Analysis of Factors that Interfere with the Regulatory Energy Process with Emphasis on the Energy Cloud - de Carvalho, Patricia Stefan; Siluk, Julio Cezar Mairesse; Schaefer, Jones Luis (International Journal of Energy Economics and Policy, 2022)
The Energy Cloud (EC) is an emerging theme that has emerged as an option to the issues of managing energy supply and demand, since it makes use of tools that streamline this process, such as cloud computing, data processing, and smart devices. Efforts need to be focused on the regulation of this energy management model and understanding what affects or delays this process which is essential for the diffusion of EC. Thus, the objective of this paper is to present and discuss, through a systematic literature review, the factors that interfere in the energy regulatory process with emphasis on EC. This research resulted in 29 Critical Success Factors (CSF), which, according to similar characteristics, were grouped into 7 Fundamental Points of View (FPV): economic, personal or socio-cultural, availability, institutional and market, regulatory infrastructure, external and information factors, and ideology. The CSFs and FPVs were cited 183 times in the selected articles. The analysis of these factors contributed to the identification of barriers that affect the energy regulatory process, delaying the development towards an EC environment, and discussed the main regulatory challenges and opportunities in this area.